Visual outcome of idiopathic epimacular membrane surgery - Globočnik Petrovič, Mojca (Zdravniški vestnik, 2010)
Background: Vitrectomy and removal of idiopathic epimacular membrane (IEM) is one of the most effective procedure in vitreoretinal surgery. The aim of our study was to evaluate the visual outcome after vitrectomy in eyes with IEM. Because of potential dose-dependent toxicity of indocyanin green (ICG) the authors compared the visual outcome after different concentration of ICG assisted vitrectomy. Methods: A retrospective analysis of visual outcome in 104 consecutively operated patients (65 female, 39 male) with IEM. The comparison in pre-operative and post-operative visual acuity, as visual gain was undertaken. Furthermore, the comparison in visual outcome between 1.25 mg/ml ICG (patients) and 0.5 mg/ml ICG (patients) assisted vitrectomy was performed. Results: Main pre-operative best corrected visual acuity (BCVA) was0.3 0.2; 0.01 - 0.8 (mean SD; min.-max.). Main post-operative BCVA 3 and 8 months after the procedure was 0.5 0.3; 0.1 - 1.00 and 0.6 0.3; 0.01- 1.00 (mean SD; min.-max.), respectively. After 8 months the mean visual gain was 0.29 0.27; -0.40 - 0.9 (mean SD; min.-max.). In comparing 1.25 mg/ ml ICG and 0.5 mg/ml ICG assisted vitrectomy there was no significantdifference in pre-operative visual acuity (p = 0.65), post-operative visual acuity after 3, 8 months (p = 0.2, p = 0.83) and visual gain after 8 months (p = 0.7). Conclusions: Vitrectomy with peeling of epiretinal membrane and ILM leads to significant improvement in visual acuity.The potential dosedependent toxicity and damage to the retina should always be kept in mind whenever using the ICG assisted vitrectomy, although wedid not found any difference in visual gain comparing the 1.25 mg/ml ICG andthe 0.5 mg/ml ICG assisted vitrectomy.
Keywords: degeneracija; Indocianin zeleno; Indocyanine Green; kirurško zdravljenje; Macular Degeneration; makula; Makula, degeneracija; oftalmologija; ostrina vida; Retrospective Studies; Retrospektivne študije; Vid, ostrina; Visual Acuity; Vitrectomy; Vitrektomija